Konflik Batin Tokoh Utama pada Miniseri Kamen Rider Snipe: Episode Zero - Erlangga, Rio Arif; Nurita, Wayan (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2024)
This research discusses the inner conflict experienced by the character Hanaya Taiga in the film Kamen Rider Snipe: Episode ZERO. This thesis uses Kurt Lewin's conflict theory and also uses qualitative methods as a research method, where the results of data analysis are in the form of descriptive word explanations. The technique used in this research is the observation and note-taking technique where the data source is analyzed and then notes related to the occurrence of inner conflict in the character Hanaya Taiga. The results of this research found that the conflicts experienced by Hanaya Taiga were type 1 conflict, type 2 conflict, and also type 3 conflict. Keywords: inner conflict; Kamen Rider; main character; miniseries. Penelitian ini bertujuan untuk membahas konflik batin yang dialami oleh tokoh Hanaya Taiga pada film Kamen Rider Snipe: Episode Zero. Penelitian ini menggunakan teori konflik dari Kurt Lewin dan juga menggunakan metode kualitatif sebagai metode penelitiannya dengan hasil analisisnya berupa penjelasan kata deskriptif. Teknik yang digunakan dalam penelitian ini adalah teknik simak dan catat. Hal-hal yang berhubungan dengan terjadinya konflik batin pada tokoh Hanaya Taiga. Hasil dari penelitian ini ditemukan bahwa konflik yang dialami Hanaya Taiga berupa konflik tipe 1, konflik tipe 2, dan juga konflik tipe 3. Kata kunci: Kamen Rider; konflik batin; miniseri; tokoh utama.